2019
DOI: 10.1107/s2052520619009260
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral tilting in the polar hexagonal tungsten bronzes RbNbW2O9 and KNbW2O9

Abstract: The ambient‐temperature structures (orthorhombic, space group Cmc21) of the polar hexagonal tungsten bronzes RbNbW2O9 and KNbW2O9 have been determined by high‐resolution powder neutron diffraction. Displacement of the A‐site cation along the polar c axis with concomitant octahedral tilting occurs to optimize the A cation bonding environment, hence reducing the coordination from 18 to 16. This effect is more evident in KNbW2O9 due to decreased A cation size. The octahedral tilting in both compositions results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The HTB oxides, ANbW 2 O 9 , A = K and Rb, also have the octahedral tilt system shown in Fig. 2c, with a lowering of space group symmetry to Cmc 2 1 to take account of polar displacements of the B -site cations (McNulty et al , 2019).…”
Section: The Htb Structurementioning
confidence: 99%
“…The HTB oxides, ANbW 2 O 9 , A = K and Rb, also have the octahedral tilt system shown in Fig. 2c, with a lowering of space group symmetry to Cmc 2 1 to take account of polar displacements of the B -site cations (McNulty et al , 2019).…”
Section: The Htb Structurementioning
confidence: 99%
“…Samples were prepared via traditional solid-state synthesis using the methodology presented in our previous work. [10] Sacrificial powder, comprised of the unreacted reagents, was used to cover the pellets to minimise alkali metal loss. Pellets for electrical measurements were mixed with a small amount of polyvinyl alcohol (PVA) solution to act as a binding agent and pressed under 200 MPa using an isostatic oil press.…”
Section: Synthesismentioning
confidence: 99%
“…In our previous work we have shown that the ambient temperature structure is orthorhombic, space group Cmc21 (a ~7.3, b ~12.7, c ~7.8 Å). [10] A minor pyrochlore impurity phase (RbNbWO6, ~1 wt. %) is present, however this was not included in refinements due to the minimal contribution to the observed diffraction pattern.…”
Section: Thermal Evolution Of the Crystal Structurementioning
confidence: 99%
See 2 more Smart Citations